2015
DOI: 10.1186/s12904-015-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pain management and psychospiritual distress in patients with advanced cancer following admission to a palliative care unit

Abstract: BackgroundAlthough many cross-sectional studies have demonstrated the association between cancer pain and psychospiritual distress, the time-dependent relationship has not been fully explored. For that reason, this study aims to investigate the time-dependent relationship between psychospiritual distress and cancer pain management in advanced cancer patients.MethodsThis is a prospective observational study. Two hundred thirty-seven advanced cancer patients were recruited from a palliative care unit in Taiwan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Pain was significantly associated with the psychological distress even after controlling performance status, age, gender, and tumor site, pain would be the only predictor . A prospective observational study also found that poor pain management may be associated with intractable depression in advanced cancer patients . Our results showed after controlling the demographic variables, clinical variables, major problem resources including physical and emotional problems, pain degree and breakthrough pain were still the predictor of psychological distress among the advanced cancer patients, and the patients with breakthrough pain reported greater HADS distress.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Pain was significantly associated with the psychological distress even after controlling performance status, age, gender, and tumor site, pain would be the only predictor . A prospective observational study also found that poor pain management may be associated with intractable depression in advanced cancer patients . Our results showed after controlling the demographic variables, clinical variables, major problem resources including physical and emotional problems, pain degree and breakthrough pain were still the predictor of psychological distress among the advanced cancer patients, and the patients with breakthrough pain reported greater HADS distress.…”
Section: Discussionsupporting
confidence: 48%
“…A logistic regression suggested that advanced cancer inpatients with breakthrough pain, higher pain degree, poorer KPS, and emotional problems may be at high risk of psychological distress. Pain was significantly associated with the psychological distress even after controlling performance status, age, gender, and tumor site, pain would be the only predictor . A prospective observational study also found that poor pain management may be associated with intractable depression in advanced cancer patients .…”
Section: Discussionmentioning
confidence: 95%
“…A substantial proportion of patients with cancer experience pain [ 1 ], which sometimes interferes with their daily lives and affects their mental health [ 2 , 3 ]. As stated in the World Health Organization (WHO) guidelines on pain relief and palliative care, assessment of pain and providing appropriate treatment for it are important aspects of pain management [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis has found a dose–response effect, indicating that higher levels of psychological distress are linked to a 41% increased risk of cancer death 4. Psycho-spiritual distress, such as anxiety, depression and hopelessness, is prevalent among patients with cancer undergoing chemotherapy 5. Approximately 32.5% to 75.7% of patients with cancer experience psycho-spiritual distress, which is higher than in the population as a whole, as well as higher than in patients with other diseases 6–8.…”
Section: Introductionmentioning
confidence: 99%